PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP INTERAKSI SOSIAL SISWA TERISOLIR KELAS X AKUNTANSI SMK MUHAMMADIYAH 2 PEKANBARU T.A 2015/2016 - Adelina Effendi; Rosmawati '; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to determine the influence of guidancegroup service towards isolated students social interaction at x accountant classmuhammadiyah vocational high school 2 Pekanbaru year 2015/2016. This researchtake place at Muhammadiyah Vocational High School 2 Pekanbaru from march 2016until may 2016. The method used in this research is real experimental method withpretest-postest control group design pattern. The subject of this research is the studentsat X Accountant 1 class, X Accountant 2 class, and X Accountant 3 class who areisolated from their friends around. The data accumulation instrument is questionnairewith guttman scale. The data analysis technic is statistic correlation technic. Based onthe wilcoxon test result there is a difference between isolated students socialinteraction before and after the guidance group service 12,1%. Later, if comparedbetween experiment group and control group based on mann-whitney test result thereis a significant difference between the interaction of isolated students towardsexperiment group and the interaction of isolated students towards control group.Key Words: Guidance Group, Social Interaction, Isolated Students